THE IMPACT OF ADMINISTRATIVE FORTIFICATION ON THE LIQUIDITY OF STOCKS IN COMPANIES LISTED IN THE IRAQI MARKET FOR SECURITIES - Tammar Salih Jawad Hayder (Galaxy International Interdisciplinary Research Journal, 2024)
This research aims to investigate the impact of administrative fortification mechanisms on the financial performance of companies listed on the Iraq Stock Exchange. The study involves a random sample of companies, and a cross-sectional time series data model will be used to analyze the data. The study involved analyzing cross-sectional time series data using two models - a fixed effect model and a random effect model. The study found that the independence of the Board of Directors x1, Administrative Ownership x2, the dual role of the Director x3, and the Term of CEO x4 are independent variables that have a significant impact on financial performance variables with a confidence factor of 95%. This was concluded by applying both the fixed effect model and the random effect model. The research aims to prove the validity of three hypotheses. The first hypothesis is that there is a fundamental relationship between administrative fortification mechanisms and the rate of return on assets, with a confidence factor of 95%. The second hypothesis is that there is an essential relationship between administrative immunization mechanisms and the rate of return on shareholders’ equity, also with a confidence factor of 95%. The third hypothesis is that there is a fundamental relationship between administrative fortification mechanisms and earnings per share, which was proven correct with a confidence factor of 95%.